MODEL DISCOVERY LEARNING BERBANTUAN GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS DAN KEMANDIRIAN BELAJAR SISWA - Maharani, Deswita; Rafianti, Isna; Novaliyosi, Novaliyosi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Mathematics, as an important foundation in education, contributes to the advancement of science and technology and teaches students logical, analytical, and creative thinking. This is in accordance with the Merdeka Curriculum which emphasizes the development of 21st century skills and character development, including critical thinking and self-regulated learning. However, the low mathematical critical thinking skills and self-regulated learning in Indonesia is still a challenge. One of the factors that influence this is the use of inappropriate learning models. The Discovery Learning learning model supported by technology such as GeoGebra is a potential solution to improve both capabilities. The purpose of this study was to determine the increase in mathematical critical thinking skills and determine the increase in self-regulated learning of students who obtained the GeoGebra-assisted Discovery Learning model compared to students who obtained conventional learning models. This research method is a quasi-experiment with the nonequivalent pre-test post-test control group design. Sampling is done by purposive sampling technique. This research was carried out in one of the Junior High Schools in Serang City in the 2023/2024 school year, involving two classes of grade VII students as an experimental and control group. The instruments in this study consisted of tests of mathematical critical thinking skills and learning independence scales. The results showed that the improvement of mathematical critical thinking skills and increased self-regulated learning of students who applied the GeoGebra-assisted Discovery Learning model were better than students who applied conventional learning models